2008
DOI: 10.18832/kp2008011
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of acrylamide in the course of malting and in beer.

Abstract: Akrylamid v potravinách vzniká v průběhu Maillardovy reakce a jeho prekurzory jsou redukující cukry a aminokyselina asparagin. Reakční mechanismus vzniku akrylamidu v potravinách závisí na složení potravin a na podmínkách zpracování.Akrylamid vzniká ve významném množství tepelnou úpravou potravin nad 120 °C, maximum akrylamidu vzniká při 150-180 °C. Při vyš-ších teplotách je vznik akrylamidu podstatně nižší, protože eliminační reakce je rychlejší než reakce vzniku akrylamidu.Surovinou pro výrobu sladu je ječme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Malt is usually kilned at temperatures for the given malt type (up to 225 °C) for 90 min to 2.5 h. Mikulíková et al [ 135 ] showed that the maximum AA formation was detected in the thermal interval 150–170 °C. Thereafter, AA formation decreases.…”
Section: Behaviour and Fate Of The Most Important Chemical Pollutants...mentioning
confidence: 99%
“…Malt is usually kilned at temperatures for the given malt type (up to 225 °C) for 90 min to 2.5 h. Mikulíková et al [ 135 ] showed that the maximum AA formation was detected in the thermal interval 150–170 °C. Thereafter, AA formation decreases.…”
Section: Behaviour and Fate Of The Most Important Chemical Pollutants...mentioning
confidence: 99%
“…LC-MS methods do not require this step, saving analyst time. Malt is usually kilned at temperatures for the given malt type (up to 225 °C) for 90 min to 2.5 h. Mikulíková et al [135] showed that the maximum AA formation was detected in the thermal interval 150-170 °C. Thereafter, AA formation decreases.…”
Section: Acrylamidementioning
confidence: 99%